Андрей Блинов: о жизни и творчестве / А. Власенко - Власенко Александр Никитич (Удмуртия, 1986)
Экземпляры: КР (20020330) / Инвентарный номер: у35161 / Сис.шифр: 8Р2 / Авт.знак: В 58 / ГРНТИ: 17 / ББК: 83